Civil Law in the Context of Inheritance: Drafting a Validand Functioning Will - Samsidar, Samsidar (Leges Privatae, 2024)
This study aims to analyze the legal responsibility of business owners in the case of work accidents and the implications of existing regulations on worker protection. Using a normative juridical approach, this study identifies and analyzes the legal provisions that govern the responsibilities of business owners based on applicable legislation, including the Manpower Law and related government regulations. Data was collected through literature studies that included legal literature, official documents, and analysis of court decisions relevant to work accident cases. The results of the study show that business owners have a significant responsibility in maintaining occupational safety, where a good understanding of regulations and the implementation of safety policies greatly affects the compliance of business owners. The study also identified that there are obstacles for business owners, especially small-scale ones, in meeting their legal obligations related to occupational safety. Therefore, this study recommends increased socialization regarding occupational safety regulations, as well as support for business owners to better understand and fulfill their legal obligations. It is hoped that the results of this research can contribute to the development of labor laws that are more responsive and effective in protecting workers' rights, as well as creating a safer work environment